Student firing tests and launches with commercial and self-made solid rocket motors. (August 2022) - Migliorino, Mario Tindaro; Aiello, Manuel; Berti, Matteo; Rotondi, Marco; D'Alessandro, Simone; Bianchi, Daniele; Jahjah, Munzer; Pizzarelli, Marco
Abstract: This paper presents work performed by students at Sapienza University of Rome regarding on-ground testing of solid rocket motors and launch of single-stage rocket models. The activities are part of a multidisciplinary project, in collaboration with the Italian Space Agency, aimed at the design, test, build, and launch of model rockets to be used as technological demonstrators and for educational purposes. Student activities included: (i) building of electronic components; (ii) designing and building of an experimental test bench; (iii) manufacturing of rocket parts and fuels; (iv) static firing tests of commercial and self-made solid rocket motors; (v) rocket launches. Self-made solid propellants were obtained as a mixture between potassium nitrate and sorbitol, yielding chamber pressures up to 20 bar and thrust up to 20 N, while commercial motors with thrust up to 90 N were tested. Additive manufacturing was employed for building specific rocket parts such as the nosecone, fins, and videocamera housing. The payload consisted in self-programmed board computers which recorded telemetry during flight. A total of four rocket launches up to 540 m have been performed. Highlights: Hands-on model rocketry educational activities are effective and inspiring. Students performed tests of commercial and self-made solid-propellant rocket motors. Rocket launches of increasing complexity up to 540 m were successfully carried out.